DETERMINANTS OF HALAL COSMETIC PURCHASE DECISIONS THROUGH ONLINE APPLICATIONS WITH THE UTAUT APPROACH (CASE STUDY OF STUDENTS OF THE FACULTY OF ECONOMICS AND ISLAMIC BUSINESS, UIN SUMATERA UTARA) - Lubis, Sofia; ,., Atika; Harahap, Muhammad IkhsaN (LPPM Universitas Trunojoyo Madura, 2025)
This study aims to analyze the factors influencing the decision to purchase halal cosmetics through e-commerce applications using the Unified Theory of Acceptance and Use of Technology (UTAUT) approach.This study employed a quantitative survey approach. The sample consisted of 100 students from the Faculty of Islamic Economics and Business, State Islamic University of North Sumatra, selected using a purposive sampling technique. Data were collected through an online questionnaire and analyzed using multiple linear regression (SPSS) and Partial Least Squares-based Structural Equation Modeling (PLS-SEM) using SmartPLS software.The results indicate that performance expectancy, social influence, and facilitating conditions significantly influence the decision to purchase halal cosmetics online. Meanwhile, effort expectancy did not show a significant effect. Keywords: UTAUT, Halal Cosmetics, E-Commerce, Purchasing Decisions, Muslim Students